PENGARUH BESARAN ANGGARAN DAN SISA ANGGARAN TAHUN SEBELUMNYA TERHADAP SERAPAN ANGGARAN BELANJA DENGAN PERUBAHAN ANGGARAN SEBAGAI PEMODERASI PADA SKPK KOTA BANDA ACEH - Aprilia, Ochi; Nadirsyah, Nadirsyah; Indriani, Mirna (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This study aims to find out how the influence of the budget size and the remaining budget of the previous year on budget absorption with budget changes as a moderating variable in SKPK Banda Aceh City. The population in this study was all SKPK of Banda Aceh City. This quantitative research employs secondary data in the form of APBD reports and regional regulations on changes to APBD for each SKPK of Banda Aceh City in 2019 2021. The data analysis method used is multiple linear regression and moderated regression analysis (MRA) using the SPSS version 24 application. Research results show that; 1) the amount of the budget does not affect the absorption of the expenditure budget, 2) the remainder of the previous year's budget affects the absorption of the expenditure budget, 3) changes to the budget have not been able to moderate the amount of the budget on budget absorption, 4) changes to the budget can moderate the remaining budget of the previous year on budget absorption shopping.